Current knowledge of the implication of lipid mediators in psoriasis - Simard, Mélissa; Morin, Sophie; Ridha, Zainab; Pouliot, Roxane (Frontiers in Immunology, 2022)
The skin is an organ involved in several biological processes essential to the organism’s proper functioning. Bioactive lipid mediators, derived from polyunsaturated fatty acids (PUFAs), constitute a complex bioactive lipid network greatly involved in skin homeostasis. Bioactive lipid mediators derived from n-3 and n-6 PUFAs have well-documented anti- and pro-inflammatory properties, and are recognized as playing numerous and complex roles in the behaviour of diverse skin diseases, including psoriasis. Studies have shown that a high intake of n-3 PUFAs can influence the development and progression of psoriasis, mainly by reducing the severity and frequency of psoriatic plaques. Herein, we provide an overview of the differential effects of n-3 and n-6 PUFAs lipid mediators and their distinct implications in the skin, particularly in psoriasis. This review summarizes current findings on lipid mediators playing a role in skin and their potential as therapeutic targets for psoriatic patients.